Penyuluhan Kasus Kejahatan Asusila dan Pornografi Pada Remaja dan Anak di Polda Bengkulu : Wilayah Polres Bengkulu Utara - Lufpi, Benyamin; Prisgunanto, Ilham (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Sex abused and pornography crimes are an emergency in a number of places in Indonesia and the victims are teenagers and children. It is acknowledged that teenagers and children are very vulnerable and weak in carrying out resistance, especially since it is known that the crime actor are adults who have strong power. Bengkulu, as an land dominated by plantations, agriculture and fisheries, has the potential for this crime to occur, and usually the victims will remain silent and do not dare report it to the polices. Beside it, cases are resolved using compensation and village customary law, not the positive law of the Republic of Indonesia. Therefore, this community service activity discusses socialization to anticipate the prevention of crimes of sex abused and pornography. The community service method involves conducting outreach, information and FGD to find out the dominant factors that cause this sex abused to exist. Activities were carried out at the North Bengkulu Police Station by providing counseling to high school and vocational high school students. In-depth FGDs were carried out with members of the North Bengkulu Police Unit, related Local Government Services, victims, perpetrators and also traditional and religious leaders. The findings show that many parties do not understand the forms and types of sex abused and pornography that exist. Likewise with the legalistic rules related to this. Insufficient socialization and non-synergistic handling between relevant stakeholders has caused this sex abused to increase. The influence of social media and gadgets also influences this deviant behavior in North Bengkulu.